PERSEPSI KONSUMEN MENGENAI KEADILAN DALAM PROSES PEMULIHAN KEGAGALAN PELAYANAN YANG BERDAMPAK PADA KESETIAAN DENGAN VARIABEL MEDIASI KEPUASAN DAN KEPERCAYAAN - , Albert Yonas Kusuma; , Dr. Suci Paramitasari Syahlani, M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research examines how fairness influences satisfaction, trust, and loyalty in service recovery context. The fairness variable then divided into procedural, distributive, and interactional fairness as shown by the prior research. A survey method was used to examine the fairness role to satisfaction, trust, and loyalty. The survey involves 100 respondents. They are the customers of celluler telecomunication and have had a complain to it during the last 3 months in Yogyakarta. Partial Least Square is used to analyze data. The study shows that satisfaction is influenced by interactional fairnes, but not by procedural and distributive fairness. Moreover, trust is influenced by interactional and distributive fairness, not by procedural fairness. This study also shows that customer satisfaction has influene to customer trust and loyalty. Still, customer trust has influence to customer loyalty.